POLITIK HUKUM PEMBATASAN IMPOR BBM NON-SUBSIDI DAN IMPLIKASINYA TERHADAP KEADILAN PERSAINGAN USAHA SWASTA - Joti Wahyu Pranoto; Sulistyandari Sulistyandari (Universitas Labuhanbatu, 2026)
This study examines the legal politics behind the Indonesian government’s policy on restricting the importation of non-subsidized fuel (BBM) and its implications for the operations of private business entities from a competition law perspective. The background of this research arises from Indonesia’s increasing dependence on imported fuel, which poses risks to the trade balance and national energy security. To address this, the government issued Circular Letter of the Ministry of Energy and Mineral Resources No. T-19/MG.05/WM.M/2025, limiting private import quotas to a maximum of 10% of the previous year’s sales volume. The study focuses on two main issues: first, how the government’s legal politics shape the formulation of this policy, and second, how the policy impacts private busThe increase in the market share of non-subsidized gasoline (from 11% in 2024 to 15% in mid-2025) and the large imports of refined petroleum products (up to 27.7 million tonnes) prompted the government to issue ESDM Circular Letter No. T-19/MG.05/WM.M/2025 to restrict imports of non-subsidized fuel and designate Pertamina as the single entry point. Tensions have arisen between the objectives of energy security and the principles of fair competition. This study aims to examine the legal-policy direction behind the formulation of the restriction on non-subsidized fuel imports and its implications for the operations of private business entities from the competition law perspective. The research method employed is normative legal research, using statutory and legal-policy approaches based on secondary data. The findings indicate that the policy reflects a state-control orientation that strengthens the role of the state-owned enterprise (Pertamina) as supply controller; quota restrictions and mandatory purchase obligations reduce the flexibility of independent importers, increase logistics costs, constrain product innovation, and have the potential to create barriers to entry and reinforce dominant positions that risk conflicting with Law No. 5/1999. The KPPU (Regulation No. 4/2023) functions as a check-and-balance mechanism. The findings underscore the need to calibrate policy so that state intervention remains proportional—preserving energy security without sacrificing the level playing field. This study provides normative input for policymakers, regulators (KPPU, ESDM), and market actors in drafting energy regulations that balance state control with healthy competition. Keywords: Legal Politics, Public Policy, Business Competition.